Akibat Hukum Terhadap Bank Atas Pembatalan Hak Tanggungan Melalui Putusan Pengadilan Berkekuatan Hukum Tetap - Hutadjulu, Ryan Dwitama; Abubakar, Lastuti; Handayani, Tri (JURNAL USM LAW REVIEW, 2023)
The research was conducted to analyze the legal impact on the position and obligations of the bank as the holder of mortgage rights (HT) for HT which has been determined to have no legal force by a court decision. With regard to lending, the existence of guarantees is a matter of sufficient concern to banks. Until now, land has been highly favored by banks as collateral for loans with mortgage rights. Cancellation of land ownership certificates can be submitted for land that has become HT. By canceling the mortgage right, the bank will lose the guarantee for the credit that has been issued, especially if the debtor is in bad credit status. Normative juridical is the method been used in this research. It is concluded from the discussion result that the legal consequences of the mortgage rights that have been determined to be non-forceable by a court decision on the position and obligations of the bank as the mortgage holder is that the bank will lose its position as preferred creditor. The cancellation of the agreement on the transfer of land rights also causes the cancellation of the mortgage agreement, considering that the object of the agreement does not meet the legal requirements of the agreement. The contractual relationship between the debtor and the bank as the creditor in the said rights agreement is considered non-existent and must be returned to its original state before the mortgage agreement. Penelitian dilakukan untuk menganalisis dampak hukum terhadap kedudukan dan kewajiban bank sebagai pemegang hak tanggungan (HT) untuk HT yang telah ditetapkan tidak memiliki kekuatan hukum oleh putusan pengadilan. Terkait pemberian kredit, keberadaan jaminan menjadi hal yang cukup diperhatikan oleh bank. Tanah hingga saat ini menjadi sangat disukai bank sebagai jaminan kredit dengan hak tanggungan. Pembatalan atas sertifikat kepemilikan atas tanah dapat diajukan terhadap tanah yang telah menjadi HT. Dengan pembatalan hak tanggungan, bank akan kehilangan jaminan atas kredit yang telah dikeluarkannya terlebih jika debitur dalam status kredit macet. Yuridis normative adalah metode penelitian yang digunakan dalam penelitian ini. Kesimpulan yang dapat diambil dari hasil pembahasan bahwa akibat hukum terhadap hak tanggungan yang telah ditetapkan tidak berkekuatan hukum oleh putusan pengadilan terhadap kedudukan dan kewajiban bank selaku pemegang hak tanggungan adalah bahwa bank akan kehilangan kedudukan sebagai kreditur preferen. Pembatalan perjanjian peralihan hak atas tanah turut menyebabkan pembatalam perjanjian hak tanggungan, mengingat objek perjanjiannya menjadi tidak memenuhi syarat sah perjanjian. Hubungan kontraktual antara debitur dan bank selaku kreditur dalam perjanjian hak tersebut dianggap tidak ada, sehingga keadaannya harus dikembalikan seperti semula.